A stress-associated protein OsSAP8 modulates gibberellic acid biosynthesis by reducing the promotive effect of transcription factor OsbZIP58 on OsKO2 - Li, Ming (Journal of experimental botany, 2022)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.